Fundamentación jurídica para normar la narcodependencia o toxicomanía y su Incidencia con los principios constitucionales - López Triana, Marcos Antonio (2015)
The research aims to establish a Legal Rationale for regulating drug dependence or addiction and its impact on constitutional principles. The research is structured as follows: In the first chapter, focuses on the problems that modern society with psychoactive substance faces, so it was necessary to hypothesize as a solution to the difficulties of research. In the second chapter, shown as reference the theoretical framework, because the fundamental theoretical base of authors from different doctrinal and legal books was taken. The third chapter is focused on the analytic-synthetic; such methods were used to determine the investigation. The fourth chapter is framed in verifying the hypothesis with the implementation of surveys and interviews in which he allowed to do data collection. The FIFTH CHAPTER makes the description of the Conclusions and Recommendations to the corresponding research solution. Finally CHAPTER SIX is structuring the project proposal which is a treatment program for people with addiction problems. And as the last item BIBLIOGRAFIA with the collection of some authors referred to the question asked.